Dismantle Rules of Lighting In Dance Creation - Herlinda Mansyur (Gondang: Jurnal Seni dan Budaya, 2022)
This research aims to provide a new discourse to the younger generation about the world of creating dance works. The field of development dance work creation has resulted in new discoveries ranging from creation methodologies to movement techniques that require dancers to improve fast. A choreographer must investigate every dance element that has been "considered" as a support in a dance performance, in addition to the body. These elements include music, clothing, make-up, lighting and artistic performances. The author, a choreographer, has created a lighting system for composing and staging the dance works he creates, one of which uses light from ultraviolet lamps, which can provide a different visual impact than the use of spotlights in dance performances. This research was internal research because this approach was a reconstruction of the author's thoughts on the lighting exploration process in every work process. The development of lighting in the staging of dance works should provide creative discourse for young choreographers in their work. So that young choreographers do not rely exclusively on exercise to create new movements. The stages of exploration involved in processing lighting vary significantly from the process of exploring the body. Lighting exploration focuses on using ultraviolet light on objects that are presentations of ideas and creative ideas. As a result, the author's development of elements that are "considered" supporters in a dance performance was presented in several dance works. Combining body techniques with ultraviolet-ray-irradiated objects takes dance performances to a new level.